Screening and Psycho-Oncological Support for Patients With Head and Neck Cancer and Brain Malignancies Before Radiotherapy With Mask Fixation: Results of a Feasibility Study - Adeberg, Sebastian; Sauer, Christina; Lambert, Lena; Regnery, Sebastian; Windisch, Paul; Zaoui, Karim; Freudlsperger, Christian; Moratin, Julius; Farnia, Benjamin; Nikendei, Christoph; Krauss, Juergen; Ehrenthal, Johannes C.; et al. (Frontiers in Psychology, 2021)
This single-center, single-arm trial investigates the feasibility of a psycho-oncological care program, which aims to reduce psychological distress and improve compliance with radiotherapy with mask fixation in patients with head and neck cancer or brain malignancies. The care program comprised (1) a screening/needs assessment and (2) the provision of a psycho-oncological intervention using imaginative stabilization techniques for distressed patients (distress due to anxiety ≥5) or in a case of subjective interest in the psycho-oncological intervention. Another allocation path to the intervention was directly through the radiation oncologist in charge who classified the patient as: in need of support to tolerate the immobilization device. Of a total of 1,020 screened patients, 257 (25.2%) patients indicated a distress ≥5 and 141 (13.8%) patients reported panic attacks. 25% of the patients reported a subjective interest in psycho-oncological support. A total of 35 patients received the psycho-oncological intervention, of which 74% were assigned by radiation oncologists. In this small patient cohort, no significant pre-post effects in terms of depression, anxiety, distress, and quality of life (mental and physical component scores) could be detected. Our results indicate a good feasibility (interdisciplinary workflow and cooperation, allocation by physicians in charge) of the psycho-oncological care program for this cohort of patients before radiotherapy with mask fixation. The screening results underline the high psychological distress and demand for psycho-oncological support. However, since the utilization of our intervention was low, future studies should reduce the barriers and improve compliance to psycho-oncological services by these patients.Clinical Trial Registration: https://www.drks.de/drks_web/setLocale_EN.do #DRKS00013493